The effectiveness of aromatherapy combination of pepperlav (peppermint and lavender) to relieve nausea vomiting in pregnant women - Isti Chana Zuliyati; Annisa Fatmawati; Sundari Mulyaningsih (Alma Ata University Press, 2023)
Background : Nausea and vomiting in first trimester pregnant women can cause symptoms of prenatal distress and stress which will affect a mother’s quality of life. Nausea and vomiting will also affect the nutritional intake of the mother and fetus. Nutritional needs that are not fulfilled from the beginning of pregnancy can cause fetal growth restriction which can cause short and long term complications and have a negative impact on quality of life.Objectives : This research aims to test the combination aromatherapy product Pepperlav (Peppermint and Lavender) in pregnant women to relieve nausea and vomiting.Methods : This study pretest-posttest control group design method with a total sample of 40 first trimester pregnant women who experienced nausea and vomiting. This research was conducted at the Midwife Independent Practice in the Bantul Region. Data collection was carried out by interviewing and filling out questionnaires that measured nausea and vomiting before and after the intervention. The questionnaire used is a valid and reliable RINVR. Intervention were carried out by administering Pepperlav Aromatherapy Combinations with formulations FIB (40:50:10), F2B (30:60:10), F3B (20:70:10) with VCO based notes that have fulfilled the physical stability, homogeneity, measurement PH, spreadability and adhesion tests, product safety tests and preference tests conducted on women who are not pregnant. Data were analyzed using the Paired t Test. Results : Based on statistical tests with Paired t test analysis p value: 0.001, this shows that the p value <0.05, there is a significant effect on the administration of pepperlav aromatherapy in Formula 1 formulation (a combination of 40% peppermint, 50% Lavender and 10% VCO. Conclusions : Aromatherapy combination of Pepperlav (peppermint and lavender) can relieve nausea and vomiting in pregnant women.